Search for scalar leptoquarks and T-odd quarks in the acoplanar jet topology using 2.5 fb(-1) of p(p)over-bar collision data at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2008)
A search for new physics in the acoplanar jet topology has been performed in 2.5 fb(-1) of data from p (p) over bar collisions at root s = 1.96 TeV, recorded by the do detector at the Fermilab Tevatron Collider. The numbers of events with exactly two acoplanar jets and missing transverse energy are in good agreement with the Standard Model expectations. The result of this search has been used to set a lower mass limit of 205 GeV at the 95% C.L. on the mass of a scalar leptoquark when this particle decays exclusively into a quark and a neutrino. In the framework of the Little Higgs model with T-parity, limits have also been obtained on the T-odd quark mass as a function of the T-odd photon mass. (C) 2008 Elsevier B.V. All rights reserved.